Modern Diagnosis and Clinical Course of Resistant Forms of Pulmonary Tuberculosis in Uzbekistan - Asadova Kamilla; Asadova Gulnara Akmalovna (Genius Journals, 2023)
Tuberculosis (TB) continues to be a significant global health concern, with millions of people affected each year. In recent years, the emergence of drug-resistant forms of pulmonary tuberculosis has posed a new challenge for healthcare systems worldwide. Uzbekistan, a country in Central Asia, is one of the nations grappling with the rising prevalence of resistant tuberculosis cases. This article aims to explore the modern diagnosis and clinical course of resistant forms of pulmonary tuberculosis in Uzbekistan, shedding light on the challenges faced and the strategies employed to combat this public health issue.
Keywords: Modern diagnosis; clinical course; resistant forms